Forest diversity and aboveground carbon linkage between the national park and community managed tropical forests of Nepal - Ranabhat, Sunita; Malla, Rajesh (Banko Janakari, 2023)
The relationship of forest diversity and aboveground carbon has been poorly explored in tropical forests under different management regimes. An assessment of the linkage between forest diversity and carbon has become important, particularly to devise effective approaches to forest management and policy formulation. To assess the relation between forest diversity and carbon stock, we correlated the structural attributes (i.e., DBH, height, wood density, and stem density), diversity attributes (i.e., species richness, Shannon Weiner index and Shannon equitability index) and aboveground carbon of tree species ≥ 5cm in DBH from Bardia National Park and adjoining Buffer zone Community Forest. Our results showed that most structural attributes are correlated to aboveground carbon in both forest types. While the diversity attributes (i.e., species richness and Shannon index) and stem density had no relation with aboveground carbon in both forests. Similarly, species evenness had a significant inverse relation with aboveground carbon in both forests. The correlation of DBH and height was stronger with aboveground carbon in community managed forest while the same was moderate in national park. In addition, the carbon stock was found slightly higher in the community managed forest than in national park. This indicates that forest structural diversity enhances the aboveground carbon in tropical forests, and community managed forest promotes the better growth of vegetation. These results provide a better insight into forest management and its effects on forest diversity and aboveground carbon.